An assessment of the Azostix strip test. Issue 1 (February 1970) - Bold, A. M.; Menzies, I. S.; Walker, G.
Abstract : The approximate concentration of urea in a single, unmeasured drop of blood may be estimated with an Azostix strip in a little over a minute, without the use of laboratory equipment. The test has been assessed by comparing 488 strip readings made by two observers on 331 specimens of blood from patients with plasma urea concentrations determined by the Auto-Analyzer diacetyl monoxime method. Observations were also made on inter- and intra-observer reading differences, on the effect of the period of contact of blood with the reagent zone of the strip and on the effect of different types of illumination. Difficulties with visual colour matching inevitably limit the performance of this type of test. Azostix strips cannot replace laboratory methods, but, provided their limitations are appreciated, and proper technique is observed, they should provide a screening test for azotaemia when laboratory facilities are not readily available. Their place in hospitals would seem to be confined to emergency use as a screening test for severe azotaemia. In general and domiciliary practice they should provide a convenient screening test for azotaemia provided that readings greater than `20 mg/100 ml' are taken as an indication for further investigation.